2011
DOI: 10.1029/2010jc006409
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale modeling of primary production and ice algal biomass within arctic sea ice in 1992

Abstract: An ice ecosystem model was coupled to a global dynamic sea ice model to assess large‐scale variability of primary production and ice algal biomass within arctic sea ice. The component models are the Physical Ecosystem Model (PhEcoM) ice ecosystem model and the Los Alamos Sea Ice Model (CICE). Simulated annual arctic sea ice primary production was 15.1 Tg C; within the range of 9 to 73 Tg C estimated using in situ data. The amount of C fixed was >3 Tg C month−1 for March, April, and May. The Bering Sea, Arctic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
99
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 40 publications
12
99
1
1
Order By: Relevance
“…In contrast, the nutrient control on ice algal production is less pronounced; although high ice algal GPP usually concides with high surface seawater nitrate, it is also present in a few areas where the nitrate levels are relatively low (Baffin Bay and Chukchi Sea; Figure 8b). Overall, ice algal production is mostly confined to shelf regions (water depth <100 m; Figure 3), consistent with previous model studies (Deal et al, 2011;Dupont, 2012;Jin et al, 2012Jin et al, , 2018 There are a few noteworthy similarities and differences in the spatial variability in modelled ice algal annual production between the present study and previous model studies. All studies show a moderate-to-high level of ice algal production in Baffin Bay.…”
Section: Spatial Variabilitysupporting
confidence: 91%
“…In contrast, the nutrient control on ice algal production is less pronounced; although high ice algal GPP usually concides with high surface seawater nitrate, it is also present in a few areas where the nitrate levels are relatively low (Baffin Bay and Chukchi Sea; Figure 8b). Overall, ice algal production is mostly confined to shelf regions (water depth <100 m; Figure 3), consistent with previous model studies (Deal et al, 2011;Dupont, 2012;Jin et al, 2012Jin et al, , 2018 There are a few noteworthy similarities and differences in the spatial variability in modelled ice algal annual production between the present study and previous model studies. All studies show a moderate-to-high level of ice algal production in Baffin Bay.…”
Section: Spatial Variabilitysupporting
confidence: 91%
“…Ice algae can also produce copious amounts of dimethylsulfoniopropionate (DMSP), the precursor of DMS, an osmotic regulator and a cryoprotectant [e.g., Tison et al, 2010]. Finally, iron concentrations in sea ice can be much higher than in the ocean and sea ice can act as a seasonal reservoir in the Southern Ocean [Lannuzel et al, 2007;2011]: growing sea ice incorporates large amounts of iron, later released into surface waters when the ice melts. This seasonal process may temporarily relieve iron limitation on phytoplankton growth, notably in the Southern Ocean [Lancelot et al, 2009], a key player in the marine carbon cycle [Sarmiento and Gruber, 2006;Sigman et al, 2010], but also in the Bering Sea [Aguilar-Islas et al, 2008] Sea ice proxies integrate information from biological, chemical and physical processes occurring in the polar oceans in an attempt to reconstruct past sea ice conditions [see Armand and Leventer, 2010, for a review].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased surface albedo (Perovich et al, 2011a), earlier melt onset, and a longer melt season (Markus et al, 2009, updated) have contributed to the observed increases in sea ice and snow melt (Perovich and Richter-Menge, 2009), and higher absorption and transmission of solar irradiance within and through Arctic sea ice Stroeve et al, 2014). Beyond the physical consequences of the observed changes, strong impacts on ecological interactions and biogeochemical processes are expected, such as changes in habitat conditions for ice-associated organisms or changes in primary production (Arrigo et al, 2012;Deal et al, 2011;Popova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%